Promoting water splitting on arrayed molybdenum carbide nanosheets with electronic modulation. Issue 37 (13th September 2021) - Diao, Jinxiang; Li, Xiaolin; Wang, Shuya; Zhao, Zejun; Wang, Weitao; Chen, Kai; Chen, Xiaoting; Chao, Tingting; Yang, Yong
Abstract : A facile strategy for the N-induced electronic-structure reformation of the molybdenum carbide nanosheet array material has been developed. This electrocatalyst showed superior activity and stability for water splitting. Abstract : Water electrolysis, driven by earth-abundant transition-metal-based electrocatalysts, is an important reaction for sustainable energy storage. Efficient water splitting processes at electrodes are kinetically limited by the improper adsorption strengths between reaction intermediates/products and electrocatalysts. Heteroatom doping could regulate the electronic structures of transition metals, thereby allowing the optimization of adsorption strengths. In this study, we report a class of arrayed molybdenum carbide nanosheets doped with strong electronegative heteroatoms, achieving excellent water splitting performance. Spectroscopic studies, including X-ray photoelectron spectroscopy and X-ray absorption near-edge structure, verified the N-induced electronic regulation on Mo2 C. In alkaline media, the arrayed N–Mo2 C/NF nanosheets realize a stable overpotential of 83.9 mV and 220 mV at 10 mA cm −2 for HER and OER, respectively, comparable to the state-of-the-art precious-metal-based electrocatalysts. Theoretical calculations show that the doping of strong electronegative nitrogen dramatically reforms the electronic structure of Mo2 C and thus optimizes the adsorption free energies of reaction intermediates in hydrogen and oxygen evolution reactions (HER/OER). This study provides a viable route and inspiration to fabricate highly efficient electrocatalysts with transition-metal based materials.